Alignment of substance use community benefit prioritization and service lines in US hospitals: a cross-sectional study - Cory E. Cronin; Luke Kubacki; Lauren Donovan; Neeraj Puro; Dakota Lavinder; Kristin Schuller; Berkeley Franz (Addiction Science & Clinical Practice, 2024)
Abstract Background Non-profit hospitals in the U.S. are required by the 2010 Patient Protection and Affordable Care Act (ACA) to conduct a community health needs assessment (CHNA) every three years and to formulate an implementation strategy in response to those needs. Hospitals often identify substance use as a need relevant to their communities in their CHNAs and then must determine whether to create strategies to address such a need within their implementation strategies. The aim of this study is to assess the relationship between a hospital’s prioritization of substance use within its community benefit documents and its substance use service offerings, while considering other hospital and community characteristics. Methods This study of a national sample of U.S. hospitals utilizes data collected from publicly available CHNAs and implementation strategies produced by hospitals from 2018 to 2021. This cross-sectional study employs descriptive statistics and multivariable analysis to assess relationships between prioritization of substance use on hospital implementation strategies and the services offered by hospitals, with consideration of community and hospital characteristics. Hospital CHNA and strategy documents were collected and then coded to identify whether the substance use needs were prioritized by the hospital. The collected data were incorporated into a data set with secondary data sourced from the 2021 AHA Annual Survey. Results Multivariable analysis found a significant and positive relationship between the prioritization of substance use as a community need on a hospital’s implementation strategy and the number of the services included in this analysis offered by the hospital. Significant and positive relationships were also identified for five service categories and for hospital size. Conclusions The availability of service offerings is related both to a hospital’s prioritization of substance use and to its size, indicating that these factors are likely inter-related regarding a hospital’s sense of its ability to address substance use as a community need. Policymakers should consider why a hospital may not prioritize a need that is prevalent within their community; e.g., whether the organization believes it lacks resources to take such steps. This study also highlights the value of the assessment and implementation strategy process as a way for hospitals to engage with community needs.